2009
DOI: 10.1111/j.1574-6941.2009.00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant species and soil type cooperatively shape the structure and function of microbial communities in the rhizosphere

Abstract: The rhizosphere is of central importance not only for plant nutrition, health and quality but also for microorganism-driven carbon sequestration, ecosystem functioning and nutrient cycling in terrestrial ecosystems. A multitude of biotic and abiotic factors are assumed to influence the structural and functional diversity of microbial communities in the rhizosphere. In this review, recent studies on the influence of the two factors, plant species and soil type, on rhizosphere-associated microbial communities ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

58
1,267
4
23

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,936 publications
(1,352 citation statements)
references
References 115 publications
58
1,267
4
23
Order By: Relevance
“…Finally, we found evidence for temporal differentiation in 3/5 comparisons (Table S11). Taken together, these data are consistent with previous evidence showing that plant and soil factors affect population structure in the rhizosphere [72].…”
Section: Discussionsupporting
confidence: 92%
“…Finally, we found evidence for temporal differentiation in 3/5 comparisons (Table S11). Taken together, these data are consistent with previous evidence showing that plant and soil factors affect population structure in the rhizosphere [72].…”
Section: Discussionsupporting
confidence: 92%
“…Though exact mechanisms for such differences are not completely understood, because these studies were all conducted on different soil types, it is likely that soil type may be one of the most important environmental variables influencing the structure of the maize root-inhabiting bacterial community at low taxonomic levels (Berg and Smalla, 2009;Castellanos et al, 2009;Garbeva et al, 2004). Growth-stage related dynamics and the differences in rhizosphere bacterial community structure from different soil types further support the general concept that plant and soil type cooperatively shape the structure of microbial community in the rhizosphere (Berg and Smalla, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Rhizosphere bacterial communities differ across plant species, soil type, root architecture and growth stage (Berg and Smalla, 2009;Marschner et al, 2001Marschner et al, , 2004. As maize (Zea mays) is an important crop, its rhizosphere bacterial community has been intensively investigated using a variety of approaches (Aira et al, 2010;Castellanos et al, 2009;Chelius and Triplett, 2001;Dohrmann et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these differences in the litter contribution influenced the soil microbial biomass across the gradient. Additionally, some studies have reported that more diverse plant communities positively affect soil microorganisms (Berg & Smalla, 2009;Wallenstein et al, 2007;Malchair et al, 2010;Lamb et al, 2011). Wallenstein et al (2007) evaluated the bacterial community between Alaskan tussock and shrub tundra vegetation and found that plant communities regulate bacterial communities through the quantity and chemical quality of plant litter in the soil.…”
Section: Discussionmentioning
confidence: 99%